PENGARUH PENGGUNAAN HANDPHONE TERHADAP AKTIVITAS BERMAIN ANAK DI LUAR RUMAH DI JORONG SILAYANG PASAMAN BARAT - Ahmad Habib Nst (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to examine the influence of cellphone use on children's play activities outside the home in Jorong Silayang, West Pasaman. The research method used is quantitative with descriptive and inferential analysis techniques. The research population was children aged 6-12 years in Jorong Silayang, West Pasaman, with a sample of 50 people taken using a purposive sampling technique. The research instrument used was a questionnaire. The results of this study show that almost all respondents have cellphones and more than half of them use cellphones to play games or watch videos. Most children only play outside a few times a week. Statistical analysis shows that there is a significant negative influence between cellphone use and children's playing activities outside the home in Jorong Silayang, West Pasaman. This finding is in line with previous research showing a relationship between cellphone use and children's low physical activity. This research can strengthen public and related parties' awareness of the impact of excessive cellphone use on children's health and lives, as well as encourage active and healthy lifestyles for children through playing activities outside the home.